2017
DOI: 10.1186/s12876-017-0622-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and functional capacity in individuals reporting overlapping symptoms of gastroesophageal reflux disease, functional dyspepsia and irritable bowel syndrome - a population based study

Abstract: BackgroundGastroesophageal reflux disease (GERD), functional dyspepsia (FD) and irritable bowel syndrome (IBS) are common functional gastrointestinal conditions with a significant impact on daily life. The objectives were to analyse general self-rated health and self-reported functional capacity in adults meeting the criteria for GERD, FD and IBS, respectively, and in individuals who meet the criteria for more than one of the conditions.MethodsA nationwide study of 100,000 individuals aged 20 years and above, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
(40 reference statements)
1
15
1
1
Order By: Relevance
“…Compared to previous research regarding SRH, a longer educational career (Kim, 2011), fewer symptoms (Jarbøl, 2017), better qualitative sleep customs (Darviri, 2011), deeper social capital (Vankova, 2016), moderate alcohol consumption (Badawi, 2012) and having medical insurance (Kim, 2011) were the same factors associated with better SRH. Regarding smoking, previous studies showed the opposite outcome.…”
Section: Discussioncontrasting
confidence: 49%
“…Compared to previous research regarding SRH, a longer educational career (Kim, 2011), fewer symptoms (Jarbøl, 2017), better qualitative sleep customs (Darviri, 2011), deeper social capital (Vankova, 2016), moderate alcohol consumption (Badawi, 2012) and having medical insurance (Kim, 2011) were the same factors associated with better SRH. Regarding smoking, previous studies showed the opposite outcome.…”
Section: Discussioncontrasting
confidence: 49%
“…Symptoms of GERD vary widely; esophageal symptoms such as heartburn and regurgitation are the most characteristic features, while gastrointestinal symptoms such as dyspepsia, epigastric pain, and somatoform disorder may also occur [3031323334353637383940414243]. Extraesophageal symptoms include cough, hoarseness, globus, and shortness of breath, and they may be associated with reflux cough syndrome, reflux laryngitis syndrome, reflux asthma syndrome, and reflux dental erosion syndrome [28444546474849505152].…”
Section: Resultsmentioning
confidence: 99%
“…Although the physician-conducted patient screening methods were carefully designed to exclude patients with IBS and FD overlap, 4/10 fulfilled FD criteria in the Rome III questionnaire, which was self-completed by patients after study entry. Inclusion of some IBS patients with co-existing FD in our study probably does not detract from our major conclusions, given how common this coexistence is[27,28]. Posserud et al[25] did not exclude IBS patients who also met diagnostic criteria for FD in their solid meal study and found no differences in meal-associated symptom provocation between their FD-negative and positive IBS patients[25].…”
Section: Discussionmentioning
confidence: 95%